(untitled) (Research, Society and Development, 2021)
Cervical lymphadenopathy is a frequent problem in pediatric patients and in many cases represents a transient reaction to locoregional or systemic inflammatory or infectious processes, considered the most common cause of peripheral lymphadenopathy in the cervical region. Biopsy associated with histopathological analysis is considered the gold standard for the diagnosis of cervical lymphadenopathy. Fine needle puncture (FNAB) has been used as the first line of investigation in the diagnosis of edema in the head and neck, as it is simple, economical and less invasive than incisional biopsy. This study was carried out through a search of scientific articles in the electronic database, PubMed, using the descriptors: Lymphadenitis; Tuberculosis, Lymph Node; Histiocytic Necrotizing Lymphadenitis, indexed dealing with clinical case reports and literature review. In addition to the review, a case report of a pediatric patient treated at the emergency department by the Oral and Maxillofacial Surgery and Traumatology was presented. tuberculoid necrotizing agent, for discussion on diagnostic and treatment approaches.